Nothern Sotho traditional healers perceptions of homosexuality : a study in the Capricorn District in Limpopo Province, South Africa - Letsoalo, Daniel Lesiba (My University, 2020)
Eurocentric literature has contributed towards the understanding of homosexuality for centuries. However, there is very little literature on perceptions of homosexuality from an African perspective. Based on this historical gap, the aim of the current study was to explore Northern Sotho traditional healers’ perceptions of homosexuality in the Capricorn District in Limpopo Province, South Africa. This was with the intention of documenting themes pertinent to Northern Sotho culture regarding homosexuality. Ten (10) participants (7 females and 3 males) were interviewed in the current study and they were selected using snowball sampling. Data was collected using individual face-to-face interviews guided by semi-structured questions and analysed using Thematic content analysis (TCA). The study was underpinned by Afrocentricity. The main themes and sub-themes which emerged from the data analysis were: homosexuality threatens family structure and values; homosexuality is regarded as a taboo and a disgrace; homosexuality and ancestral calling; historical evidence of homosexuality; homosexuality is confusing; homosexuality and western culture; homosexuality and cleansing (mourning process); homosexuality, traditional healing and ancestral calling; homosexuality and initiation schools as well as proposed interventions to curb homosexuality. The results of the study suggest that understanding homosexuality is not consistent with Northern Sotho culture. The study contributes to knowledge and information within Northern Sotho culture and offers suggestions for indigenous knowledge systems (IKS), academic training, policy development and legislation in terms of homosexuality and the indigenous culture. The study also offers guidelines, which health care workers and any other relevant personnel who work closely with homosexuals, should be cognisant of. Furthermore, valuable lessons were also reasoned from the current study in terms of homosexuality and Northern Sotho culture in the area where the research took place.
Thesis (Ph. D. (Psychology)) -- University of Limpopo, 2020
Keywords: Afrocentricity; Culture; Homosexuality; Northern Sotho; Traditional Healer; Homosexuality -- South Africa -- Limpopo; Homosexuality -- Psychological aspects; Healers; Afrocentrism